ChemInform Abstract: Highly Enantioselective Aza‐Michael Reaction Between Alkyl Amines and β‐Trifluoromethyl β‐Aryl Nitroolefins. Issue 17 (April 2016) - Wang, Leming; Chen, Jiean; Huang, Yong
Abstract: Chiral N‐heterocyclic carbenes are used as noncovalent organocatalysts for the highly selective aza‐Michael addition between primary alkyl amines and various nitroolefins affording chiral trifluoromethylated amines.